Preparation method and application of silicon-carbon negative electrode material
By reacting metal salt with sodium silicate in the negative electrode material of lithium-ion battery to generate silica with more atomic vacancies and mixing them with graphene, the problem of degradation of cyclic performance of silicon-based anode materials in lithium-ion batteries is solved, and the specific capacity and cyclic performance are improved.
Patent Information
- Application Number
- CN202210105519.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-28
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-01-28
AI Technical Summary
The cycling performance of silicon-based anode materials in lithium-ion batteries is affected by structural damage and crushing caused by volume expansion and contraction, which affects the specific energy and cycle life of the battery.
The silicate precipitate is formed by reacting the metal salt solution with the sodium silicate solution, and the metal ions are removed and silica with more atomic vacancies. It is then mixed with graphene and heated under an inert atmosphere to form a silicon-carbon composite negative electrode material.
This method effectively alleviates the problem of degradation in circulation performance caused by volume expansion, and improves the specific capacity and circulation performance of the material by forming single silicon with higher specific capacity.
Smart Images

Figure CN114551851B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery negative electrode materials, and particularly relates to a preparation method and application of a silicon-carbon negative electrode material. Background Art
[0002] Lithium-ion batteries have become a research hotspot due to their high specific capacity, high charge-discharge efficiency, excellent cycle performance, and low cost. The rapid development of electronic products and new energy vehicle technologies has placed higher demands on lithium-ion batteries. Anode materials, as a crucial component of lithium-ion batteries, influence the battery's specific energy and cycle life requirements and have long been a key focus of lithium-ion battery research. With the advancement of lithium-ion battery technology, the demand for high capacity and small size has become increasingly prominent. Therefore, the development of new high-capacity anode materials is urgent.
[0003] In the research and application of lithium-ion battery negative electrode materials, silicon-based negative electrode materials have higher lithium storage capacity and lower voltage platform, and are one of the hot spots in the research of lithium-ion battery negative electrode materials. Silicon-based materials have the highest theoretical specific capacity, and the alloys they form are Li x Si, x ranges from 0 to 4.4. The theoretical specific capacity of pure silicon is 4200mAh / g, while the theoretical capacity of natural graphite, the current commercial negative electrode material, is only 372mAh / g. In addition, silicon has no solvation effect, its raw material reserves are abundant, and it has higher stability than other metal materials. It is considered to be the most anticipated high-capacity lithium-ion battery negative electrode material.
[0004] However, silicon anodes undergo significant volume expansion and contraction during lithium insertion and removal cycles, which damages and pulverizes the material structure. This leads to the delamination of the electrode sheet, resulting in loss of electrical contact between the electrode active material and the current collector, severely impacting the battery's cycling performance. Furthermore, silicon itself is a semiconductor material with very low electrical conductivity. These issues have hindered the large-scale application of silicon-based anode materials in lithium-ion batteries.
[0005] To address the problem of silicon negative electrode materials being prone to stress cracking during charge and discharge, which causes volume expansion and deteriorates cycle performance, the following main improvement methods are currently available: reducing the particle size of active silicon particles and preparing nanoscale materials to reduce the internal stress caused by volume change; using composites of nano-silicon materials and other materials, such as silicon-carbon composites, to alleviate the volume expansion of silicon, thereby improving its cycle life. Related technologies provide a material composed of carbon nanofibers and silicon materials, which, when used as a negative electrode material for lithium-ion batteries, has improved capacity and cycle performance. Some scholars have also used hot gas deposition to coat a layer of carbon material on the surface of silicon alone, achieving a specific capacity of more than 600mAh / g and cycle performance comparable to that of carbon materials, which is significantly improved compared to the cycle performance of single-substance silicon. However, when using silicon-based negative electrodes for lithium-ion battery negative electrodes, their capacity and cycle performance still need to be improved compared to the theoretical capacity of silicon materials. Summary of the Invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a preparation method of a silicon-carbon negative electrode material and its application.
[0007] According to one aspect of the present invention, a method for preparing a silicon-carbon negative electrode material is provided, comprising the following steps:
[0008] S1: adding a metal salt solution to a sodium silicate solution to react, aging the solution after the reaction, and performing solid-liquid separation to obtain a silicate precipitate;
[0009] S2: calcining the silicate precipitate to obtain a calcined material;
[0010] S3: placing the calcined material in concentrated acid for heat soaking, followed by solid-liquid separation and water washing to obtain a wet material;
[0011] S4: adding the wet material to a graphene dispersion, evaporating to dryness, and heating the obtained dry material under an inert atmosphere to obtain the silicon-carbon negative electrode material.
[0012] In some embodiments of the present invention, in step S1, the metal salt solution is at least one of a solution of a soluble magnesium salt, an aluminum salt, a nickel salt or a manganese salt.
[0013] In some embodiments of the present invention, in step S1, the metal salt solution is added to the sodium silicate solution at a rate of 5-20 mL / min.
[0014] In some embodiments of the present invention, in step S1, the concentration of the metal salt solution is 0.5-2.5 mol / L.
[0015] In some embodiments of the present invention, in step S1, the concentration of the sodium silicate solution is 0.1-1.0 mol / L in terms of SiO2.
[0016] In some embodiments of the present invention, in step S1, the amount of sodium silicate used is 1.05-1.1 times the theoretical amount.
[0017] In some embodiments of the present invention, in step S1, the reaction temperature is 70-95°C.
[0018] In some embodiments of the present invention, in step S1, the aging time is 1-2 hours.
[0019] In some embodiments of the present invention, in step S2, the calcination temperature is 700-1200° C. Further, the calcination time is 1-2 hours.
[0020] In some embodiments of the present invention, in step S3, the concentration of the concentrated acid is 4-12 mol / L, the temperature of the hot soak is 60-120° C., and the time of the hot soak is 10-120 min.
[0021] In some embodiments of the present invention, in step S3, the liquid-to-solid ratio of the concentrated acid to the calcined material is 1-3 mL / g.
[0022] In some embodiments of the present invention, in step S3, the concentrated acid is at least one of sulfuric acid, hydrochloric acid or nitric acid.
[0023] In some embodiments of the present invention, in step S4, the graphene dispersion is prepared by ultrasonically dispersing graphene in an organic solvent, and the mass ratio of silicon dioxide to graphene in the wet material is (0.05-0.2):1.
[0024] In some preferred embodiments of the present invention, in step S4, the organic solvent is at least one of methanol, ethanol, acetone, tetrahydrofuran, NMP, DMF, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate.
[0025] In some preferred embodiments of the present invention, in step S4, the concentration of the graphene dispersion is 0.5-3.0 g / L.
[0026] In some embodiments of the present invention, in step S4, the heating process is: first heating to 350-450° C. and keeping warm for 1-2 hours, then heating to 800-1300° C. and keeping warm for 5-12 hours.
[0027] The present invention also provides application of the preparation method in preparing lithium ion batteries.
[0028] According to a preferred embodiment of the present invention, there are at least the following beneficial effects:
[0029] 1. The present invention first generates a silicate precipitate by reacting a metal salt with sodium silicate, and then calcining the precipitate at high temperature to crystallize the silicate. The metal ions are then removed by hot soaking in concentrated acid to obtain silicon dioxide with more atomic vacancies. The silicon dioxide is mixed with graphene. Under oxygen-isolating conditions, the graphene captures oxygen atoms from the silicon dioxide to further form oxygen-containing functional groups, while the silicon dioxide is reduced to silicon element, thereby obtaining a silicon-carbon composite negative electrode material.
[0030] 2. Since the silicon dioxide produced after the metal ions are removed from the silicate has more atomic vacancies, when used as a negative electrode material, it can effectively alleviate the problem of decreased cycle performance caused by volume expansion. Moreover, when sintered with graphene, the silicon dioxide is deprived of oxygen atoms to form elemental silicon with higher specific capacity, thereby improving the specific capacity and cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0032] Figure 1 This is an SEM image of the silicon-carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following will clearly and completely describe the concept and technical effects of the present invention in conjunction with the embodiments to fully understand the purpose, features and effects of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0034] Example 1
[0035] This embodiment prepares a silicon-carbon negative electrode material, and the specific process is as follows:
[0036] Step 1, preparing a magnesium chloride solution A with a metal ion concentration of 1.0 mol / L;
[0037] Step 2, preparing a sodium silicate solution B with a concentration (in terms of SiO2) of 1.0 mol / L;
[0038] Step 3: adding the magnesium chloride solution A prepared in step 1 to the sodium silicate solution B prepared in step 2 at a rate of 10 mL / min to carry out the reaction, controlling the reaction temperature to 70° C., and using an amount of sodium silicate of 1.05 times the theoretical amount;
[0039] Step 4: After the reaction is completed, continue aging for 2 hours;
[0040] Step 5, separating the material into solid and liquid to obtain a solid material;
[0041] Step 6, calcining the solid material at a temperature of 1200° C. for 2 hours to obtain a calcined material;
[0042] Step 7: Soak the calcined material in 12 mol / L sulfuric acid at a liquid-to-solid ratio of 1 mL / g for 60 min at a temperature of 120° C.
[0043] Step 8, separating the material into solid and liquid, and then washing with pure water to obtain a wet material;
[0044] Step 9, graphene is weighed according to a mass ratio of silicon dioxide to graphene in the wet material of 5%, and ultrasonically dispersed in ethanol to obtain a graphene dispersion with a graphene concentration of 3.0 g / L;
[0045] Step 10, adding the wet material to the graphene dispersion, stirring evenly, and evaporating to dryness to obtain a powder material;
[0046] Step 11: heat the powder material to 450° C. under inert gas and keep it warm for 2 hours, then heat it to 800° C. and keep it warm for 5 hours to obtain a silicon-carbon negative electrode material.
[0047] Example 2
[0048] This embodiment prepares a silicon-carbon negative electrode material, and the specific process is as follows:
[0049] Step 1, preparing aluminum sulfate solution A with a metal ion concentration of 2.0 mol / L;
[0050] Step 2, preparing a sodium silicate solution B with a concentration (in terms of SiO2) of 0.5 mol / L;
[0051] Step 3: adding the aluminum sulfate solution A prepared in step 1 to the sodium silicate solution B prepared in step 2 at a rate of 20 mL / min to carry out a reaction, controlling the reaction temperature to 85° C., and using an amount of sodium silicate of 1.05 times the theoretical amount;
[0052] Step 4: After the reaction is completed, continue aging for 1 hour;
[0053] Step 5, separating the material into solid and liquid to obtain a solid material;
[0054] Step 6, calcining the solid material at a temperature of 1100° C. for 2 hours to obtain a calcined material;
[0055] Step 7: Soak the calcined material in 8 mol / L hydrochloric acid at a liquid-to-solid ratio of 2 mL / g for 120 min at a temperature of 60° C.
[0056] Step 8, separating the material into solid and liquid, and then washing with pure water to obtain a wet material;
[0057] Step 9, graphene is weighed according to a mass ratio of silicon dioxide to graphene in the wet material of 10%, and ultrasonically dispersed in acetone to obtain a graphene dispersion with a graphene concentration of 0.5 g / L;
[0058] Step 10, adding the wet material to the graphene dispersion, stirring evenly, and evaporating to dryness to obtain a powder material;
[0059] Step 11: heat the powder material to 350° C. under inert gas and keep it warm for 2 hours, then heat it to 1000° C. and keep it warm for 8 hours to obtain a silicon-carbon negative electrode material.
[0060] Example 3
[0061] This embodiment prepares a silicon-carbon negative electrode material, and the specific process is as follows:
[0062] Step 1, preparing nickel sulfate solution A with a metal ion concentration of 2.5 mol / L;
[0063] Step 2, preparing a sodium silicate solution B with a concentration (in terms of SiO2) of 0.1 mol / L;
[0064] Step 3: adding the metal salt solution A prepared in step 1 to the sodium silicate solution B prepared in step 2 at a rate of 5 mL / min to carry out the reaction, controlling the reaction temperature to 95° C. and using an amount of sodium silicate of 1.1 times the theoretical amount;
[0065] Step 4: After the reaction is completed, continue aging for 2 hours;
[0066] Step 5, separating the material into solid and liquid to obtain a solid material;
[0067] Step 6, calcining the solid material at 700° C. for 2 h to obtain a calcined material;
[0068] Step 7: Soak the calcined material in 4 mol / L nitric acid at a liquid-to-solid ratio of 3 mL / g for 120 min at a temperature of 70° C.
[0069] Step 8, separating the material into solid and liquid, and then washing with pure water to obtain a wet material;
[0070] Step 9, weighing graphene according to a mass ratio of silicon dioxide to graphene in the wet material of 20%, and ultrasonically dispersing it in tetrahydrofuran to obtain a graphene dispersion with a graphene concentration of 1.0 g / L;
[0071] Step 10, adding the wet material to the graphene dispersion, stirring evenly, and evaporating to dryness to obtain a powder material;
[0072] Step 11: heat the powder material to 400° C. under inert gas and keep it warm for 2 hours, then heat it to 1200° C. and keep it warm for 12 hours to obtain a silicon-carbon negative electrode material.
[0073] Comparative Example 1
[0074] This comparative example prepared a silicon-carbon negative electrode material. The difference from Example 1 is that the wet material was replaced with commercially available nano-scale silicon dioxide powder (analytical grade, 5-20 nm). The specific process is as follows:
[0075] Step 1, graphene is weighed according to a mass ratio of silicon dioxide powder to graphene of 5%, and ultrasonically dispersed in ethanol to obtain a graphene dispersion with a graphene concentration of 3.0 g / L;
[0076] Step 2: adding silicon dioxide powder to the graphene dispersion, stirring evenly, and evaporating to dryness to obtain a powder material;
[0077] Step 3: Heat the powder material to 450° C. under inert gas and keep it warm for 2 hours, then heat it to 800° C. and keep it warm for 5 hours to obtain a silicon-carbon negative electrode material.
[0078] Comparative Example 2
[0079] This comparative example prepared a silicon-carbon negative electrode material. The difference from Example 2 is that the wet material was replaced with commercially available silicon dioxide powder (analytical grade). The specific process is as follows:
[0080] Step 1, graphene is weighed according to a mass ratio of silicon dioxide powder to graphene of 10%, and ultrasonically dispersed in acetone to obtain a graphene dispersion with a graphene concentration of 0.5 g / L;
[0081] Step 2: adding silicon dioxide powder to the graphene dispersion, stirring evenly, and evaporating to dryness to obtain a powder material;
[0082] Step 3: Heat the powder material to 350° C. under inert gas and keep it warm for 2 hours, then heat it to 1000° C. and keep it warm for 8 hours to obtain a silicon-carbon negative electrode material.
[0083] Comparative Example 3
[0084] This comparative example prepared a silicon-carbon negative electrode material. The difference from Example 3 is that the wet material was replaced with commercially available silicon dioxide powder (analytical grade). The specific process is as follows:
[0085] Step 1, graphene is weighed according to a mass ratio of silicon dioxide powder to graphene of 20%, and ultrasonically dispersed in tetrahydrofuran to obtain a graphene dispersion with a graphene concentration of 1.0 g / L;
[0086] Step 2: adding silicon dioxide powder to the graphene dispersion, stirring evenly, and evaporating to dryness to obtain a powder material;
[0087] Step 3: Heat the powder material to 400° C. under inert gas and keep it warm for 2 hours, then heat it to 1200° C. and keep it warm for 12 hours to obtain a silicon-carbon negative electrode material.
[0088] Test example
[0089] The silicon-carbon negative electrode materials obtained in Examples 1-3 and Comparative Examples 1-3 were mixed with a conductive agent (SP) and a binder (CMC / SBR) to prepare an electrode slurry. The slurry was evenly coated onto a 9μm-thick copper foil current collector, dried under vacuum at 105°C for 12 hours, and then cut to produce negative electrode sheets. 2032-type button cells were assembled in a glove box filled with high-purity argon. The charge and discharge performance of the button cells was tested with a charge and discharge cutoff voltage range of 5mV-1.5V and a test temperature of 25°C. The test results are shown in Table 1.
[0090] Table 1
[0091]
[0092]
[0093] As can be seen from Table 1, the specific capacity and cycle performance of the comparative example are lower than those of the example. This is because after the silicate precipitate of the example is soaked in concentrated acid and hot to remove metal ions, the resulting silicon dioxide has more atomic vacancies. When used as a negative electrode material, it can effectively alleviate the problem of decreased cycle performance caused by volume expansion. At the same time, more atomic vacancies can accommodate more lithium, and the specific capacity is improved.
[0094] While the embodiments of the present invention have been described in detail above with reference to the accompanying drawings, the present invention is not limited to the embodiments described above. Various modifications may be made within the scope of knowledge possessed by a person skilled in the art without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof may be combined with one another unless there is a conflict.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1: adding a metal salt solution to a sodium silicate solution for reaction, aging after the reaction is completed, and performing solid-liquid separation to obtain a silicate precipitate; S2: calcining the silicate precipitate to obtain a calcined material; S3: placing the calcined material in concentrated acid for heat soaking, then solid-liquid separation and water washing to obtain a wet material, wherein the concentration of the concentrated acid is 4-12 mol / L; the temperature of the heat soaking is 60-120°C; S4: adding the wet material to the graphene dispersion, evaporating to dryness, and heating the obtained dry material under an inert atmosphere to obtain the silicon-carbon negative electrode material. The heating process is: first heating to 350-450° C. and keeping warm for 1-2 hours, and then heating to 800-1300° C. and keeping warm for 5-12 hours.
2. The preparation method according to claim 1, characterized in that: In step S1, the metal salt solution is at least one of a soluble magnesium salt, an aluminum salt, a nickel salt or a manganese salt solution.
3. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the metal salt solution is 0.5-2.5 mol / L.
4. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the sodium silicate solution is 0.1-1.0 mol / L in terms of SiO2.
5. The preparation method according to claim 1, characterized in that: In step S1, the reaction temperature is 70-95°C.
6. The preparation method according to claim 1, characterized in that: In step S2, the calcination temperature is 700-1200°C.
7. The preparation method according to claim 1, characterized in that: In step S4, the graphene dispersion is prepared by ultrasonically dispersing graphene in an organic solvent, and the mass ratio of silicon dioxide to graphene in the wet material is (0.05-0.2):
1.
8. Use of the preparation method according to any one of claims 1 to 7 in the preparation of lithium ion batteries.
Citation Information
Patent Citations
Method for preparing silicon-based composite anode material of lithium ion battery
CN104681798A
Preparation method of carbon-silicon negative electrode material and lithium ion battery
CN107910540A